SIMULATION: CONCEPTUAL ISSUES - Pazin Filho, Antonio; Romano, Minna Moreira Dias (Medicina (Ribeirao Preto), 2007)
Simulation demands the elaboration of the information to be transmitted, including decomposing the task in several components that should obey sequency. The information should be presented respecting four basic principles: exposition, sequence, feed-back and repetition.